MANAJEMEN PERUBAHAN DALAM TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) PEMERINTAHAN DI INDONESIA (Sebuah Pemikiran Dalam Menyongsong Peralihan e-Government Menjadi e-Governance) - Gafar, T. Fahrul (Departemen Ilmu Pemerintahan FISIP UNPAD, 2017)
For more than a decade the program e-Government or use and utilization of Teknonogi Information and Communication Technology (ICT) in Indonesia implemented since the issuance of the Presidential Instruction (Presidential Instruction no 3 of 2003 on the National Strategy and Policy Development of e-Government of Indonesia. But then the performance of the e-Government Indonesia has not yet found an ideal performance. A fact and data stated that in the year 2016 Indonesia rated to 116 world version e-Government Development Index (EGDI), down 10 stages compared to the year 2014 which ranked to 106. This condition is still far under the countries in Southeast Asia such as Singapore (stages the 4), Malaysia (60th stage), the Philippines (stages to-71), and Brunei Darussalam (ranked 83th birthday). Meanwhile, the value of the Online Service Index (OSI), and Telecommunication Infrastructure Index (BAWAH) Indonesia also is still below the regional average of Asia. Indonesia is located on numbers 0,3623 on OSI, and 0,3016 on Transparency International Indonesia, while in the Asian region the average OSI on numbers 0,5120 and Transparency International Indonesia on numbers 0,3730. Through this writing, author attempt to offer some ideas to follow rentak and rhythm of the emergence of new theories in science that seems to the government cannot be expected to again be a player or single agent in e-Government development program, but sinergitas one of four players going around the large orbit named governance (styler-kelolaan) together with private parties who have creativity, among universities academics/ professionals who have the ideas and the idea of smartphone, and society widely, so that the government of the owner the authority is able to guarantee the implementation of all celebration with unrest and with the result that deserves.